Microplastics Study of Microplastic Concentrations at the Drinking Water Depot in Sumbersari Village, Jember Regency - Tri Wahyuni, Rahajeng; Nurika, Globila (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Microplastics are a new pollutant that has become a global problem and requires treatment as soon as possible. Microplastics are plastic waste that degrades into small particles measuring <5 mm. Until now, microplastics have not only been found in the environment but also in drinking water. Based on the results of field studies, it is known that drinking water refills at drinking water depots (DAM) are an alternative option used by the people of the Sumbersari sub-district to meet their drinking water needs. This paper examines the presence of microplastics in refillable drinking water, including the characteristics, concentration, and exposure to microplastics in consumers of refillable drinking water. This observational study uses descriptive methods to systematically examine and present facts regarding microplastics and exposure to microplastics in DAM in the Sumbersari sub-district. The research showed that microplastics had contaminated 12 DAM with an average microplastic concentration of 7.1 particles/liter. The forms or types of microplastics found were fibers and fragments with sizes ranging from 0.01 mm to <5 mm and the colors most commonly found were blue, black, red, gray, and transparent. The measurement results also explain that consumers of refillable drinking water will be exposed to microplastics of at least 5.61 particles/liter/day and a maximum of 15.98 particles/liter/day, depending on the amount of drinking water consumed daily.